PERBAIKAN SISTEM PENTANAHAN INSTALASI LISTRIK DENGAN KARBON AKTIF KULIT PADI DAN GARAM DI DESA KEDUNGMEGARIH KEC. KEMBANGBAHU KABUPATEN LAMONGAN - Zainal Abidin; Abdurrahman Wahid; Ahmad Fauzi Maulana (ABDI KAMI: Jurnal Pengabdian Kepada Masyarakat, 2020)
Dissemination of the results of research conducted in the village of Kedungmegarih, Kembangbahu Lamongan, which taken as samples to conduct experiments in fields that have dry soil conditions with an average depth of springs more than 100 m, in conditions it is far from standard electric grounding which requires resistance conditions low ground. Moist or wet soil structures are ideal conditions where soil resistance is low, so that electric grounding is a condition stated in PUIL 2000 that the recommended grounding of the building insulation is a minimum of 5Ω and a maximum of 10Ω. The method used in the implementation of the dissemination is to modify the grounding system in the installation of several houses in Kedungmegarih Kembangbahu by using the activated charcoal salt system as an alternative model for modifying soil conditions to obtain lower soil resistance. Based on the results of the dissemination in the field, it can be concluded that grounding water, salt and activated charcoal with a size of 5: 2: 1 produces an average resistance value of 1.52Ω, and an average of 2.43Ω on wet lime soil. Compared to the method without modification The average value of active charcoal in soil is 3Ω and 3.5Ω on lime soils. Grounding using water, salt and activated charcoal can reduce grounding efficiency by 75% in lime soils and 65% in solid soils.